Creating sustainable health care systems: Agreeing social (societal) priorities through public participation. Issue 1 (18th March 2019) - Littlejohns, Peter; Kieslich, Katharina; Weale, Albert; Tumilty, Emma; Richardson, Georgina; Stokes, Tim; Gauld, Robin; Scuffham, Paul
Abstract : Purpose: In order to create sustainable health systems, many countries are introducing ways to prioritise health services underpinned by a process of health technology assessment. While this approach requires technical judgements of clinical effectiveness and cost effectiveness, these are embedded in a wider set of social (societal) value judgements, including fairness, responsiveness to need, non-discrimination and obligations of accountability and transparency. Implementing controversial decisions faces legal, political and public challenge. To help generate acceptance for the need for health prioritisation and the resulting decisions, the purpose of this paper is to develop a novel way of encouraging key stakeholders, especially patients and the public, to become involved in the prioritisation process. Design/methodology/approach: Through a multidisciplinary collaboration involving a series of international workshops, ethical and political theory (including accountability for reasonableness) have been applied to develop a practical way forward through the creation of a values framework. The authors have tested this framework in England and in New Zealand using a mixed-methods approach. Findings: A social values framework that consists of content and process values has been developed and converted into an online decision-making audit tool. Research limitations/implications: The authors have developed an easy to use method to help stakeholders (including the public) to understand the need for prioritisation of health services and to encourage their involvement. It provides a pragmatic way of harmonising different perspectives aimed at maximising health experience. Practical implications: All health care systems are facing increasing demands within finite resources. Although many countries are introducing ways to prioritise health services, the decisions often face legal, political, commercial and ethical challenge. The research will help health systems to respond to these challenges. Social implications: This study helps in increasing public involvement in complex health challenges. Originality/value: No other groups have used this combination of approaches to address this issue.